Knowledge, perception and practices regarding novel coronavirus among sample of Ghanaian healthcare workers: a cross-sectional study - Serwaa, Dorcas; Appiah, Anthony Baffour; Wodag-Seme, Richard; Nkansah, Charles; Ahiatrogah, Selasie (International Journal Of Community Medicine And Public Health, 2021)
Background: Healthcare workers’ have increased risk of contracting the deadly COVID-19 pandemic due to their exposures to infected persons and their specimens. Ghana, like many other countries, has felt the devastating effects of this virus; it was therefore prudent to assess the levels of knowledge, perception and practice of Ghanaian healthcare providers on the current pandemic. Methods: This descriptive cross-sectional study enlisted 979 healthcare workers’ in Ghana from 1st Apr to 20th Nov, 2020, via self-reported questionnaire. SPSS version 22.0 was used for the analysis. Responses were summarized using frequency and proportions. A chi-square test was utilized to test for association at significant level of p <0.05. Results: Out of the 979 healthcare workers recruited, 56.4% had good knowledge and 59.5% displayed good perception on the novel COVID-19 while 63.1% of them effectively practiced the expected precautionary measures. Age (p=0.001), gender (p=0.034) and profession (p<0.001) significantly affected the practice of precautionary measure among the health personnel. The respondents’ perceptions towards the pandemic were significantly linked to their age (p<0.001), gender (p=0.043), profession (p<0.001), type of occupation (p=0.001) and source of information (p=0.006). Also, knowledge significantly related to good practices but did not influence the perception of HCWs. Conclusions: The current study identifies that more than half of HCWs in Ghana have sufficient knowledge, perception, and practice of precautionary measures; however, it elucidates some significant concerns about the knowledge gap in this COVID-19 outbreak. There is an obvious need for progressive in-service training programs for the health workers to broaden their scopes on the risks and preventive measures.